ANALISIS PENGARUH KINERJA LINGKUNGAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) (Studi Empiris pada perusahaan yang terdaftar di Daftar Efek Syariah 2012-2015) - Windi Asmara; Safira Almunawar (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
This research aims to examine the effect of environmental performance, profitability, company size, and leverage on the disclosure of islamic social reporting. This research was performed on companies listed in the List of Islamic Securities. The population in this research were 227 companies in the period 2012-2015. Samples were taken using purposive sampling method. Sample meeting the criteria as many as 26 companies. Methods of data analysis using multiple linear regression analysis. The results of this research indicate that the size of the company's and environmental performance are significant effect on the disclosure of islamic social reporting, while profitability and leverage no significant effect on the disclosure of islamic social reporting companies listed in the List of Islamic Securities.